2008
DOI: 10.1158/1055-9965.epi-07-2518
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Tumor and Matched Normal Tissues from Non-Small Cell Lung Cancer Patients

Abstract: We used MethyLight assays to analyze DNA methylation status of 27 genes on 49 paired cancerous and noncancerous tissue samples from non-small cell lung cancer (NSCLC) patients who underwent surgical resection. Seven genes (RARB, BVES, CDKN2A, KCNH5, RASSF1, CDH13, and RUNX) were found to be methylated significantly more frequently in tumor tissues than in noncancerous tissues. Only methylation of CCND2 and APC was frequently detected in both cancerous and noncancerous tissues, supporting the hypothesis that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 33 publications
4
115
3
1
Order By: Relevance
“…have reported that its promoter methylation almost exclusively occurred in tumor cells (6,7). Also, MGMT inactivation through hypermethylation contributes to a large fraction of p53 mutation in NSCLC, including G : C A : T transition (8,9), which is known to be one of the most important tumor suppressor genes in human.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have reported that its promoter methylation almost exclusively occurred in tumor cells (6,7). Also, MGMT inactivation through hypermethylation contributes to a large fraction of p53 mutation in NSCLC, including G : C A : T transition (8,9), which is known to be one of the most important tumor suppressor genes in human.…”
Section: Resultsmentioning
confidence: 99%
“…methylguanine-DNA methyltransferase (MGMT) protect cells from this mutation by transferring the alkyl group from the O 6 -guanine in DNA to an active cysteine within its own sequence (1). Hypermethylation of the promoter region of MGMT gene has been reported to be the most frequent mechanism of MGMT inactivation (2)(3)(4).…”
mentioning
confidence: 99%
“…Concomitant methylation of multiple genes is common, particularly in cancerous tissues, which is strongly associated with lung cancer risk [33,34]. In the present study, we identified a panel of the nine hypermethylated genes with excellent specificity and sensitivity, which were only methylated in cancerous tissues but not in noncancerous tissues.…”
Section: Discussionmentioning
confidence: 64%
“…Hypermethylation of the CDH1 promoter has been postulated to play a critical role in the loss of E-cadherin expression observed in some primary tumors and cell lines without identifying CDH1 mutations. CDH1 promoter hypermethylation has been reported in Non-small cell lung cancer, prostate, thyroid, gastric, and other cancers (Tamura et al, 2000;Feng et al, 2008;Ramezani et al, 2012). The finding that treatment of cell lines with demethylating agents can, in some cases, restore E-cadherin expression suggests that in some tumors, promoter hypermethylation plays an important role in silencing of CDH1 expression.…”
Section: Discussionmentioning
confidence: 99%